Answer:
no no no! don't touch me there that is my no no square
Step-by-step explanation:
Answer:2/3
Step-by-step explanation:
Simplifying
(9m + -6) * 7 = 0
Reorder the terms:
(-6 + 9m) * 7 = 0
Reorder the terms for easier multiplication:
7(-6 + 9m) = 0
(-6 * 7 + 9m * 7) = 0
(-42 + 63m) = 0
Solving
-42 + 63m = 0
Solving for variable 'm'.
Move all terms containing m to the left, all other terms to the right.
Add '42' to each side of the equation.
-42 + 42 + 63m = 0 + 42
Combine like terms: -42 + 42 = 0
0 + 63m = 0 + 42
63m = 0 + 42
Combine like terms: 0 + 42 = 42
63m = 42
Divide each side by '63'.
m = 0.6666666667
Simplifying
m = 0.6666666667=2/3 when simplified
Answer:
okay i need to know the options
Step-by-step explanation:
of right angle triangle! .
<u>Step-by-step explanation:</u>
Here we have , A student is asked to find the length of the hypotenuse of a right triangle. The length of one leg is 32 centimeters, and the length of the other leg is 25 centimeters. The student incorrectly says that the length of the hypotenuse is 7.5 centimeters. We need to find:
A)
We have , One length as 32 cm and other as 25 cm , as
![Perpendicular = 32cm\\Base=25cm](https://tex.z-dn.net/?f=Perpendicular%20%3D%2032cm%5C%5CBase%3D25cm)
By Pythagoras Theorem ,
⇒ ![Hypotenuse^2 = Perpendicular^2+Base^2](https://tex.z-dn.net/?f=Hypotenuse%5E2%20%3D%20Perpendicular%5E2%2BBase%5E2)
⇒ ![Hypotenuse^2 =32^2+22^2](https://tex.z-dn.net/?f=Hypotenuse%5E2%20%3D32%5E2%2B22%5E2)
⇒ ![\sqrt{Hypotenuse^2} =\sqrt{1024+484}](https://tex.z-dn.net/?f=%5Csqrt%7BHypotenuse%5E2%7D%20%3D%5Csqrt%7B1024%2B484%7D)
⇒ ![Hypotenuse =39cm](https://tex.z-dn.net/?f=Hypotenuse%20%3D39cm)
So ,
of right angle triangle! .